2018
DOI: 10.1002/mop.31197
|View full text |Cite
|
Sign up to set email alerts
|

A high gain broadband transmitarray antenna using dual‐resonant E‐shaped element

Abstract: A high‐gain and broadband linear‐polarized transmitarray antenna is proposed in this paper, and its element is composed of 4 identical layers of E‐shaped patches separated by quarter‐wavelength air gaps. To cover the required phase range, the dual‐resonant E‐shaped element is developed; realizing broadband transmission, low cross‐polarization level, and stable oblique‐incident response. A transmitarray prototype using the 4‐layer E‐shaped element is designed, fabricated, and tested. The proposed transmitarray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…For the past few years, considerable research works on transmitarrays have been conducted for various applications and many interesting designs have been consequently proposed with impressive performance [1][2][3][4][5][6][7]. To realise a satisfactory transmission magnitude and phase, conventional transmitarray unit-cells are usually designed in a multi-layer structure, which is high-profile and complicates the fabrication of the antenna [8][9][10][11][12][13][14][15]. In order to decrease the element profile, various techniques have been proposed [16][17][18][19][20][21] and one effective approach is to employ vertical vias connecting conductive layers printed on the substrate [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…For the past few years, considerable research works on transmitarrays have been conducted for various applications and many interesting designs have been consequently proposed with impressive performance [1][2][3][4][5][6][7]. To realise a satisfactory transmission magnitude and phase, conventional transmitarray unit-cells are usually designed in a multi-layer structure, which is high-profile and complicates the fabrication of the antenna [8][9][10][11][12][13][14][15]. In order to decrease the element profile, various techniques have been proposed [16][17][18][19][20][21] and one effective approach is to employ vertical vias connecting conductive layers printed on the substrate [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike reflectarray antennas, the feed of transmitarrays locates opposite to the radiation direction therefore the blockage effect is eliminated. 5,6 During the past few decades, considerable research efforts have been made to design transmitarray elements for a transmission phase covering 360 together with a high transmission magnitude, such as employing double square ring element, 7 spiral-dipole element, 8 rectangular ring slot element, 9 double ring slot element, 10 Eshaped element, 11 and circular patch with outer ring element. 12 It is observed that above-mentioned designs feature a multilayer structure, which increases the fabrication complexity as well as the overall thickness and the cost.…”
Section: Introductionmentioning
confidence: 99%